2014
DOI: 10.1071/an12432
|View full text |Cite
|
Sign up to set email alerts
|

Separate feeding of calcium improves performance and ileal nutrient digestibility in broiler chicks

Abstract: Abstract.A total of 144 Cobb 500 broilers were used to investigate if modern commercial broilers could regulate their calcium (Ca) intake using choice feeding and whether separating the delivery of a portion of the Ca from the mixed ration would be advantageous for performance and nutrient recovery. Birds were fed corn+soy-based diets formulated to contain 2.5, 5.0, 7.5 or 10.0 g/kg total Ca and all groups had access to a separate Ca source (CaCO 3 ). The trial was conducted from Day 1 to Day 21 and birds had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 31 publications
6
38
3
1
Order By: Relevance
“…High dietary Ca concentrations adversely influenced apparent nutrient digestibility (Underwood & Suttle, 2001). The current findings are in general agreement with previous reports (Rao et al, 2006;Tancharoenrat & Ravindran, 2014;Wilkinson et al, 2014). One possible explanation for the negative effects of high Ca may be the increase in pH in the upper gastrointestinal tract.…”
Section: Resultssupporting
confidence: 83%
“…High dietary Ca concentrations adversely influenced apparent nutrient digestibility (Underwood & Suttle, 2001). The current findings are in general agreement with previous reports (Rao et al, 2006;Tancharoenrat & Ravindran, 2014;Wilkinson et al, 2014). One possible explanation for the negative effects of high Ca may be the increase in pH in the upper gastrointestinal tract.…”
Section: Resultssupporting
confidence: 83%
“…The negative effect of high dietary Ca on N digestion in poultry, while in agreement with the findings Shafey and McDonald (1991a, b) and Wilkinson et al (2014), is not readily explainable. It may be speculated that the increased pH in the gastric phase created by the provision of high levels of Ca as limestone (Ca carbonate), a source with extremely high acidbinding capacity (Lawlor et al, 2005), may be partly responsible.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, reducing dietary Ca may increase nutrient digestibility of poultry diets by decreasing the intestinal pH as well as the formation of Ca-phosphate precipitates and improving pepsin efficacy (Selle et al, 2009;Walk et al, 2012). Wilkinson et al (2013) demonstrated that broilers fed diets with reduced Ca concentrations were able to broadly meet their Ca requirement via the consumption of a separate Ca source. However, the influence of nPP on the Ca-specific appetite of broilers and their ability to meet their Ca requirement through the consumption of a separate Ca source has not previously been reported.…”
Section: Discussionmentioning
confidence: 97%
“…Given the choice, poultry are able to self-select a balanced diet from different and complementary sources to meet their nutrient requirements. Recently, Wilkinson et al, (2013) demonstrated that contemporary broilers were able to broadly meet their Ca requirement when fed diets with as little as 0.25% Ca and a concurrent source of Ca. Coupled with this result were improved performance and increased apparent digestibility of DM, amino acids, and minerals, suggesting that this Ca-specific appetite may be able to be commercially exploited to enhance performance and possibly welfare of broilers.…”
Section: Effect Of Dietary Nonphytate Phosphorus and Calcium Concentrmentioning
confidence: 99%